1999
DOI: 10.1046/j.1464-5491.1999.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms in Chinese patients with Type 2 diabetes mellitus

Abstract: Up to 70% of the Chinese Type 2 diabetic outpatients have GI symptoms, which is a much higher rate than in non-diabetic control subjects. Duration of diabetes is the most important factor associated with the presence of such GI symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
2
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 25 publications
4
56
2
5
Order By: Relevance
“…Gastrointestinal s���to�s are re�orte�l� �o��on in �iabeti� �atients an� s���to�s are also frequent in in�i�i�uals �ithout ���� Therefore, this stu�� �eter�ine� �hether these GI s���to�s are �ore frequent in the �iabeti� �o�ulation of Qatar an� also assesse� the asso�iation bet�een GI �isor�ers an� �s��hologi�al �istress�� The �otential asso�iation bet�een GI s���to�s an� �s�-�hologi�al �istress in �iabetes has not been stu�ie� in this region�� It is i��ortant to assess the effe�t of GI s���-to�s on the �s��hologi�al �rofile for in�i�i�ual s���-to�s in �iabeti� �atients be�ause the �o-o��urren�es of �s��hologi�al �isor�ers an� gastrointestinal s���to�s �ontribute to a high �e�i�al utilization in �ri�ar� health �are settings�� Co-�orbi�it� see�s to �la� an essential role in in�reasing s���to�s�� The stu�� �ete�te� higher le�els of gastrointestinal s���to�s in the �iabeti� �o�ulation �ith �e�ression an� anxiet� �o��are� to the general �o�ulation�� Ho�e�er, �atients �ith �iabetes are al�ost t�i�e as likel� to suffer fro� anxiet� an� �e�ression than the general �o�ulation [1�] �� In the stu�� sa��le, the �re�alen�e of se�ere �e�res-sion (9��5% vs 4��4%, , P <� 0��001)� an� anxiet� (2���3% <� 0��001)� an� anxiet� (2���3% 0��001)� an� anxiet� (2���3% 0��001)� an� anxiet� (2���3% vs 1�.��%) was significantly higher in diabetic patients than in the health� �o�ulation�� �oloski et al [17] re�orte� that �s��hologi�al �istress is linke� to ha�ing �ersistent GI s���to�s an� frequentl� seeking health �are�� �ore than half of the �iabeti� �atients (58��3%)� e�aluate� re�orte� at least t�o or �ore troubleso�e GI s���to�s, �hi�h is very close to the figure reported in a study by Talley et al [18] (40%), with a significant difference with the healthy subje�ts�� An in�rease� �re�alen�e of GI s���to�s in �atients �ith �iabetes �as re�orte� in the stu�� sa��le �hi�h is in agree�ent �ith �re�ious stu�ies [1,19] �� In a Chinese �iabeti� �o�ulation [20] , it �as foun� that 70% of the� ha� GI s���to�s �hi�h �as �u�h higher than in their non-�iabeti� �ontrols�� The �ifferen�e in GI s���-toms prevalence among studies depends on the specific �iabeti� �o�ulation�� The �ajorit� of the �iabeti� �atients (39��3%)� �ith gastrointestinal s���to�s �ere obser�e� in the age grou� 45-54 �ears�� -54 �ears�� 54 �ears�� In our �iabeti� �o�ulation, �atients �ere �ore �e-�resse� �ith the GI s���to�s of anal blo�kage (4���5% vs 20��0%)�, heartburn (41��9% ��0%)�, heartburn (41��9% %)�, heartburn (41��9% vs 12��5%)�, <� 3 bo�els��k 3 bo�els��k 3 bo�els��k (51��2% vs 18��8%)�, �� 3 bo�els�� (48��8% 3 bo�els�� (48��8% 3 bo�els�� (48��8% vs 20��0%)�, earl� ��0%)�, earl� %)�, earl� satiet� (41��9% vs 5%)� an� fe�al in�ontinen�e (37��2% vs 5%)� �o��are� to health� subje�ts�� In a stu�� b� �olaski et al [17] , it �as foun� that in�rease� le�els of �s��hologi-�al �istress �ere asso�iate� �ith �ersistent GI s���to�s, in �arti�ular ab�o�inal �ain, �onsti�ation an� bloating, �hi�h is si�ilar to our stu�� results�� �e �ort et al [21] in�i-�ate� that GI s���to�s �ere �onsi�erabl� higher in the �iabeti� �o�ulation �ith 17��9% for �iarrhea, 1���1% for �onsti�ation, 19���% for bloating an� 12��5% for earl� satiet��� B�tzer B�tzer…”
Section: Discussionsupporting
confidence: 66%
“…Gastrointestinal s���to�s are re�orte�l� �o��on in �iabeti� �atients an� s���to�s are also frequent in in�i�i�uals �ithout ���� Therefore, this stu�� �eter�ine� �hether these GI s���to�s are �ore frequent in the �iabeti� �o�ulation of Qatar an� also assesse� the asso�iation bet�een GI �isor�ers an� �s��hologi�al �istress�� The �otential asso�iation bet�een GI s���to�s an� �s�-�hologi�al �istress in �iabetes has not been stu�ie� in this region�� It is i��ortant to assess the effe�t of GI s���-to�s on the �s��hologi�al �rofile for in�i�i�ual s���-to�s in �iabeti� �atients be�ause the �o-o��urren�es of �s��hologi�al �isor�ers an� gastrointestinal s���to�s �ontribute to a high �e�i�al utilization in �ri�ar� health �are settings�� Co-�orbi�it� see�s to �la� an essential role in in�reasing s���to�s�� The stu�� �ete�te� higher le�els of gastrointestinal s���to�s in the �iabeti� �o�ulation �ith �e�ression an� anxiet� �o��are� to the general �o�ulation�� Ho�e�er, �atients �ith �iabetes are al�ost t�i�e as likel� to suffer fro� anxiet� an� �e�ression than the general �o�ulation [1�] �� In the stu�� sa��le, the �re�alen�e of se�ere �e�res-sion (9��5% vs 4��4%, , P <� 0��001)� an� anxiet� (2���3% <� 0��001)� an� anxiet� (2���3% 0��001)� an� anxiet� (2���3% 0��001)� an� anxiet� (2���3% vs 1�.��%) was significantly higher in diabetic patients than in the health� �o�ulation�� �oloski et al [17] re�orte� that �s��hologi�al �istress is linke� to ha�ing �ersistent GI s���to�s an� frequentl� seeking health �are�� �ore than half of the �iabeti� �atients (58��3%)� e�aluate� re�orte� at least t�o or �ore troubleso�e GI s���to�s, �hi�h is very close to the figure reported in a study by Talley et al [18] (40%), with a significant difference with the healthy subje�ts�� An in�rease� �re�alen�e of GI s���to�s in �atients �ith �iabetes �as re�orte� in the stu�� sa��le �hi�h is in agree�ent �ith �re�ious stu�ies [1,19] �� In a Chinese �iabeti� �o�ulation [20] , it �as foun� that 70% of the� ha� GI s���to�s �hi�h �as �u�h higher than in their non-�iabeti� �ontrols�� The �ifferen�e in GI s���-toms prevalence among studies depends on the specific �iabeti� �o�ulation�� The �ajorit� of the �iabeti� �atients (39��3%)� �ith gastrointestinal s���to�s �ere obser�e� in the age grou� 45-54 �ears�� -54 �ears�� 54 �ears�� In our �iabeti� �o�ulation, �atients �ere �ore �e-�resse� �ith the GI s���to�s of anal blo�kage (4���5% vs 20��0%)�, heartburn (41��9% ��0%)�, heartburn (41��9% %)�, heartburn (41��9% vs 12��5%)�, <� 3 bo�els��k 3 bo�els��k 3 bo�els��k (51��2% vs 18��8%)�, �� 3 bo�els�� (48��8% 3 bo�els�� (48��8% 3 bo�els�� (48��8% vs 20��0%)�, earl� ��0%)�, earl� %)�, earl� satiet� (41��9% vs 5%)� an� fe�al in�ontinen�e (37��2% vs 5%)� �o��are� to health� subje�ts�� In a stu�� b� �olaski et al [17] , it �as foun� that in�rease� le�els of �s��hologi-�al �istress �ere asso�iate� �ith �ersistent GI s���to�s, in �arti�ular ab�o�inal �ain, �onsti�ation an� bloating, �hi�h is si�ilar to our stu�� results�� �e �ort et al [21] in�i-�ate� that GI s���to�s �ere �onsi�erabl� higher in the �iabeti� �o�ulation �ith 17��9% for �iarrhea, 1���1% for �onsti�ation, 19���% for bloating an� 12��5% for earl� satiet��� B�tzer B�tzer…”
Section: Discussionsupporting
confidence: 66%
“…[5][6][7] In line with previous studies, 5,7 our study showed that nearly two-thirds of patients with long duration of diabetes had at least one GI symptom. Among the GI symptoms, "stomach or belly visibly larger after meals" is the most common, while "vomiting" is the least common, which corresponded well to the previous study.…”
Section: Discussionsupporting
confidence: 92%
“…1 The cumulative 10-year incidence of gastroparesis has been estimated at 1% in type 2 diabetes among community patients with diabetes; 2 however, the prevalence of GI symptoms in diabetic patients are much higher. [3][4][5] Although the prevalence of GI symptoms varies between different studies due to different study populations and different scales of GI symptoms, most population-based studies found that GI symptoms were increased in diabetic patients as compared with nondiabetic controls. [5][6][7] GI symptoms of gastroparesis can adversely affect pharmacokinetics of oral glucose lowering drugs and the absorption of food which can lead to postprandial hypoglycemia in patients who are receiving insulin treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] Traditionally, GI symptoms in diabetic patients have been attributed to disordered motor function as a result of the irreversible autonomic neuropathy that frequently accompanies long-standing disease. 15 However, in a longitudinal study, progression of autonomic dysfunction and long standing disease were not associated with any slowing of gastric emptying.…”
Section: Introductionmentioning
confidence: 99%